Analysis Of Human Error Risk Factors In The Implementation Of The Regional Government Information System (SIPD) In Regional Financial Management Of Tegal Regency Government - Novita Dyan Saputri; Raissha Andini; Rimi Gusliana Mais (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
The implementation of the Regional Government Information System (SIPD) represents a strategic initiative by the Indonesian government to improve transparency, accountability, effectiveness, and efficiency in regional financial management through digital transformation. Despite its benefits, the implementation of SIPD remains vulnerable to human error risks that may affect the quality of financial administration and reporting. This study aims to identify and analyze human error risk factors in the implementation of SIPD within the regional financial management system of the Tegal Regency Government. A qualitative descriptive approach was employed using document analysis as the primary data collection method. Data were obtained from official government documents, including the 2023 Regional Government Financial Statements (LKPD), Notes to Financial Statements (CaLK), Government Agency Performance Reports (LKjIP), Audit Board of Indonesia (BPK) audit reports, regional regulations, and other relevant policy documents. The data were analyzed through content analysis to identify patterns and indicators of human error associated with SIPD implementation. The findings reveal that SIPD has contributed to the integration and digitization of regional financial management processes. However, several human error risk factors were identified, including asset recording inaccuracies, account classification adjustments, data inconsistencies, administrative delays, weaknesses in internal control, and limitations in user competence. These risks are primarily associated with the complexity of financial data management, insufficient system understanding, and inadequate coordination among stakeholders. To mitigate these risks, the Tegal Regency Government has implemented technical guidance programs, monitoring and evaluation mechanisms, inter-agency coordination, and strengthened internal control systems. This study contributes to the literature on digital public financial management by highlighting the importance of human factors in the successful implementation of government information systems and providing practical recommendations for enhancing SIPD effectiveness in regional governments.